Case Report: THSD7A-Positive Membranous Nephropathy Caused by Tislelizumab in a Lung Cancer Patient - Chen, Minjiang; Zhang, Lei; Zhong, Wei; Zheng, Ke; Ye, Wei; Wang, Mengzhao (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs) became the standard treatment for many different kinds of cancers and can result in a variety of immune-related adverse events (irAEs). IrAEs of kidney are uncommon and consists of different pathology types. Among the different types, membranous nephropathy (MN) is rare and have not been well-described. Since MN can also be associated with malignancies (1), differential diagnosis in patients receiving ICIs who develop MN can be very difficult. We present the case of a 74-year-old man with metastatic non-small cell lung cancer who developed MN after ICIs therapy. The patient tested positive for thrombospondin type-1 domain-containing 7A antibodies (THSD7A) when diagnosed with MN. Supplementary examinations revealed the predisposing antigen in the primary tumor and present of the antibody after immunotherapy, which corresponded to the patient's clinical course of nephropathy. Treatment consisting of systemic glucocorticoids and rituximab resulted in a good clinical response, and the THSD7A antibodies were no longer detected. In this case, we first discuss the potential mechanism of immunotherapy related MN, in which the activation of humoral immunity may play an important role.